Analisis Determinan Kejadian Penyakit Infeksi Saluran Pernapasan Akut (ISPA) pada Balita Usia 0 – 59 Bulan di Puskesmas Perumnas Kota Kendari Tahun 2015 - Nangi, Guntur (Jurnal Gizi Ilmiah, 2016)
Upper Respiratory Tract Infections for Toddlers at the Perumnas Public Health Center have increased in the last 3 years, namely in 2012 totaling 854 cases, in 2013 amounting to 901 cases and in 2014 totaling 1015 cases. And also still relatively high where the ratio of visits to toddlers and cases of Upper Respiratory Tract Infections under five who received treatment for the period January - March 2015 was 283 to 201 or 7 to 5, where every 7 visits there were 5 cases of Upper Respiratory Tract Infections under five. This study aims to determine the relationship between knowledge, exclusive breastfeeding, immunization status, nutritional status and exposure to cigarette smoke on the incidence of Upper Respiratory Tract Infections in children aged 0-59 months at the Public Health Center of Kendari City. This research is an observational study with a cross sectional study design. The population in this study was 283 people, with a non-probability sampling technique, namely accidental sampling, with a total sample of 166 people. The method of analysis used chi-square statistical test and logistic regression. The results showed that the value of X2 arithmetic > X2 table (3.841) and p < (0.05), there was a relationship between knowledge and value (X2hit = 53.320 and p = 0.000), exclusive breast milk showed a value (X2hit = 56.020 and p = 0.000 , immunization status showed a value (X2hit = 16,130 and p = 0.000, nutritional status showed a value (X2hit = 7,210 and p = 0.007), and exposure to cigarette smoke showed a value (X2hit = 6,914 and p = 0.009), which means Ho is rejected and Ha The results of the logistic regression of the most dominant factors related were knowledge of OR = 19.839 and exclusive breast milk OR = 17.464 while the less dominant factors were immunization status OR = 2.579, nutritional status OR = 1.416 and exposure to cigarette smoke OR = 1.061. Based on the results of these studies, it can be concluded that there is a relationship between the independent variable and the dependent variable. It is hoped that mothers who have children under five, as well as the community in the working area of ​​the Perumnas Health Center, will be proactive in seeking information. about ARI disease, as well as the factors that influence the incidence of ARI under five in order to take preventive measures, so that toddlers are not easily affected by upper respiratory tract infections, it is also highly expected that intensive counseling from health workers so that cases of upper respiratory tract infections in toddlers can be reduced.